PENYELESAIAN KASUS TERHADAP TINDAK PIDANA PENGANIAYAAN OLEH ANAK MELALUI DIVERSI DALAM MENERAPKAN RESTORATIF JUSTICE DI KEPOLISIAN RESOR BULELENG - Kadek Teguh Werdi; Dewa Gede Sudika Mangku; Ni Putu Rai Yuliartini (Jurnal Ilmu Hukum Sui Generis, 2023)
This study aims to: (1) know the process and reasons for carrying out diversion in handling cases of abuse by children at the Buleleng Police; (2) find out the form of restorative justice for children in cases of abuse both as perpetrators and victims in Buleleng Regency. This type of research uses empirical studies, using the nature of descriptive research. The location of this research was carried out at the Buleleng Police. Data collection techniques are by using document study techniques, interviews and observations. The results of the study show: (1) can find out the process and reasons for carrying out diversion in handling cases of abuse of children at the Buleleng Police in general running smoothly. (2) can be intended according to the procedures regulated by the diversion regulations. Can find out the form of for children in cases of abuse both as perpetrators and victims in Buleleng Regency when peace is achieved between the two parties, namely the perpetrators and victims.